(3EYQGH GdbQBfs - (3GdRLGL , EHQGgje Hf GdSQj Hf Sgd, CHhESMGb,J (B311 (3g` s
(3ChdgG (B:s
(3hbhdg Ld hYR (B" (3CaG ef Cgd GdbQi Gf jCJjge HCSfG HjJkG (B" (3ef ShQI GdEYQGa s
(3BNQgG (B:s
(3aCeG eG bhdge (B: (3de Gddg TYKc aJGhjdg (B: (3LeY Gddg dc eG jPgH TYKc Je GdLRA jJdhg bhdg (B: (3Ld hYR (B:" (3hCbe GdUdGI WQai GdfgGQ(B" s
(3abO ef Ch GdLRA GdQGHY hGdYTQje cQGSIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B40 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B33s
(3JHUQGJ GdCUd (B:s
(3HgG NQe s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdfMhs